2008
DOI: 10.4314/eamj.v85i5.9618
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing The Use Of Episiotomy During Vaginal Delivery In South Eastern Nigeria

Abstract: Background: Given considerable evidence that routine episiotomy increases maternal morbidity and without evidence to support maternal or neonatal benefit, has episiotomy use changed among health care providers? To date, very limited information exists relating to the past and current practice of episiotomy in many developing countries. Results: There were 1877 episiotomies, for an episiotomy rate of 45%. Ninety per cent of the primigravid parturients had episiotomy. Women undergoing episiotomy were younger (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 14 publications
(19 reference statements)
2
23
1
6
Order By: Relevance
“…However our results were against the studies done by Marie et al who found that episiotomies and lacerations were more likely if a women was 30 years or older and chigbu et al who showed that women undergoing episiotomy were younger than women without episiotomy [11,12].…”
Section: Discussioncontrasting
confidence: 97%
“…However our results were against the studies done by Marie et al who found that episiotomies and lacerations were more likely if a women was 30 years or older and chigbu et al who showed that women undergoing episiotomy were younger than women without episiotomy [11,12].…”
Section: Discussioncontrasting
confidence: 97%
“…10,19 Historically, the procedure episiotomy has been indicated in circumstances such as abnormal labour progression, non-reassurance fetal heart rate pattern, vacuum delivery and shoulder dystocia. 2,18 It is also believed to hasten the second stage of labour and reduce the risk of spontaneous perineal tearing, subsequent pelvic floor dysfunction, urinary and faecal incontinence, and sexual dysfunction. 2 On the other hand, however recent studies have shown that common indications for episiotomy were based on limited data.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]18 Additionally, there was a general underestimation of potential adverse consequences associated with the procedure, including extension to a third or fourth degree tear, unsatisfactory anatomical results, increased blood loss, anal sphincter dysfunction, perineal pain and painful sex. [1][2][3]18 Unfortunately, by traditional obstetric practice, women are not necessarily informed of the specific risks and benefits associated with performing episiotomy, and rarely is written consent obtained, somehow abrogating the standard set for every other surgical procedure. Recent reviews have therefore conclusively determined that the routine use of episiotomy should be abandoned and evidenced based techniques that reduce the risk of perineal trauma during childbirth should be embraced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elastisitas perineum yang semakin meningkat, episiotomi tidak lagi selalu perlu dilakukan. 22 Perineum pada primipara cenderung lebih kaku dibandingkan pada multipara karena belum pernah teregang sebelumnya pada persalinan terdahulu. Perineum yang kaku dan tidak elastis akan menghambat persalinan kala II dan dapat meningkatkan resiko terhadap janin, juga menyebabkan robekan perineum yang luas sampai tingkat III.…”
Section: Gambar 1 Rancangan Penelitianunclassified